Drone based phenotyping for rice - CGIAR Research Program on Rice (2021)
Training materials including classroom and hands-on field exercises for drone phenotyping were developed and delivered to multiple global partners. Drone-phenotyping was implemented across multiple sites and years on Reference and Antenna panels). Drone data from these trials was processed, analyzed and compiled for inclusion in global GxExM analysis.